Analisis Kontrastif Fonologi Bahasa Jawa Dialek Temanggung dan Bahasa Jawa Dialek Banyumas - Rahayu, Aditya; Meliyana, Riska; Mukaromah, Sayidah Luthfi Nur; Hutabarat, Elisa Natika; Baehaqi, Imam (Universitas Negeri Surabaya, 2025)
This study aims to study the phonological variation between Temanggung and Banyumas dialects of Javanese, focusing on vowel and consonant sound changes and phonemic processes that occur in speech. Through a qualitative descriptive approach, data was collected using observation, recording, and direct data collection methods from daily conversations as well as a Swadesh vocabulary list that includes 450 words. The results showed significant variations in the pronunciation of vowel sounds, such as the change of vowel /ͻ/ to /a/, vowel /e/ to /a/, vowel /a/ to /e/, and the variation of vowel /o/ to /u/. In addition, phoneme addition phenomena such as paragogue and prothesis, phoneme reduction (affresis), as well as vowel phoneme substitution are identified as distinctive characteristics of both dialects. These findings emphasize the importance of understanding dialectal variation in the context of phonology, as well as its implications for language teaching and local culture preservation.